MODEL PENDUKUNG KEPUTUSAN PEMASARAN MENGGUNAKAN FUZZY INFERENCE SYSTEM (STUDI KASUS: TOKO ONLINE) - Michael Setiawan; Triwulandari SD; Pudji Astuti (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2016)
The growth of Internet users both in the world and Asia give a big opportunities to develop Ecommercein Indonesia, create more Online Shops. Through the early research in the form of questionaire and interview,Online Shops have many challanges not only from competitors but also from the environment condition, Rupiahto United States Dollar rates, and also the supply condition or supplier when supplying products. To support theOnline Shops in making decisions, designed a model using Fuzzy Inference System with Mamdani because, it isintuitive and work well with human input, the model designed using MATLAB application, and for the inputs wewill be using Stock Condition, Demand Prediction from hystorical data, Ruiah to US Dollar rates, and Supplycondition, and for the outputs there will be Add stocks policy, promotional policy, contract with other supplierpolicy and price adaptation policy, for the rules we will be using the if the rules. The Models will be verified andvalidated with help from “Ikelashop” owner, the verification process will test if the rules given, give outputs asdesigned, for the validation will be using Extreme Combination Test, or using extreme combination betweencondition, face validity with help from expert to validate the outputs from Extreme Combination Test, and TuringTest with comparing between model’s output and expert decision. The result are two types of Decision SupportModel for marketing, Critical Model and Non Critical Model that is not affected by Rupiah to Dollar Rates,already verified and validated.